2017
DOI: 10.1016/j.envres.2017.07.026
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal particulate air pollution exposure and body composition in urban preschool children: Examining sensitive windows and sex-specific associations

Abstract: Background Evolving animal studies and limited epidemiological data show that prenatal air pollution exposure is associated with childhood obesity. Timing of exposure and child sex may play an important role in these associations. We applied an innovative method to examine sex-specific sensitive prenatal windows of exposure to PM2.5 on anthropometric measures in preschool-aged children. Methods Analyses included 239 children born ≥37 weeks gestation in an ethnically-mixed lower-income urban birth cohort. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
54
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 57 publications
5
54
2
Order By: Relevance
“…Two duplicate studies conducted by the same lead authors using the same dataset were identified, one study was retained as environmental measures were included in the fully adjusted model, whereas they were not in the other study. In total, eight studies were included in the narrative synthesis . Four studies were based in the United States, one each in Canada, Denmark, England, and South Korea.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Two duplicate studies conducted by the same lead authors using the same dataset were identified, one study was retained as environmental measures were included in the fully adjusted model, whereas they were not in the other study. In total, eight studies were included in the narrative synthesis . Four studies were based in the United States, one each in Canada, Denmark, England, and South Korea.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies recruited women during pregnancy, one study recruited shortly after birth, one study used a combination of the two, one study recruited 9 months after birth, and one study recruited children through schools . The recruitment rate varied between 12% and 78% (mean 51%) and was not presented in two studies . The percentage of the recruited sample who participated at each outcome time‐point varied between 22% and 83% (mean 60%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations